Safety of Tyrosine Kinase Inhibitors in Patients With Differentiated Thyroid Cancer: Real-World Use of Lenvatinib and Sorafenib in Korea - Kim, Soo Young; Kim, Seok-Mo; Chang, Hojin; Kim, Bup-Woo; Lee, Yong Sang; Chang, Hang-Seok; Park, Cheong Soo (Frontiers in Endocrinology, 2019)
Background: Thyroid cancer has become the most common cancer in Korea. Generally, thyroid cancer patients have a good prognosis; however, 15%–20% of patients experience recurrence or distant metastasis or are refractory to standard treatment. We assessed the safety of sorafenib and lenvatinib in patients with advanced or metastatic radioactive iodine-refractory differentiated thyroid cancers (DTC) consecutively treated at a tertiary center in South Korea. Methods: We retrospectively reviewed the charts of all consecutive patients with DTC treated during ≥6 months with lenvatinib (February 2016–April 2018) and sorafenib (January 2014–April 2018) at Gangnam Severance Hospital. Patients were treated according to the prescribing information of each drug and were followed up for 2 months. We evaluated the adverse events (AEs) reported with each drug. Results: A total of 71 medical records (lenvatinib, n=23; sorafenib, n=48) were reviewed. The most common histological types were papillary thyroid cancer (69.0%) and follicular thyroid cancer (22.5%). All patients (n=23) started lenvatinib at a dose of 20 mg; 41.7% of sorafenib-treated patients received an initial dose of 800 mg daily. Four (17.4%) lenvatinib-treated patients and 26 (54.2%) sorafenib-treated patients required treatment discontinuation. The most common AEs of any grade in the lenvatinib group were diarrhea (82.6%), hypertension (78.3%), hand-foot skin reaction (56.5%), weight loss (52.2%), proteinuria (47.8%), and anorexia (43.5%). In the sorafenib group, these were hand-foot skin reaction (87.5%), diarrhea (62.5%), anorexia (60.4%), alopecia (56.3%), mucositis (52.1%), weight loss and generalized weakness (each, 50%), and hypertension (43.8%). The incidence of hand-foot skin reaction, alopecia, and rash of any grade was significantly lower (P=0.003, P=0.017, and P=0.017) in patients treated with lenvatinib compared with those treated with sorafenib. The incidence of hypertension, QT prolongation, and proteinuria of any grade was significantly higher (P=0.006, P=0.038, and P<0.001) in patients treated with lenvatinib compared with those treated with sorafenib. Seven deaths occurred, which were attributed to disease progression. Conclusions: No new safety concerns were identified for either drug. Most AEs were managed with dose modification and medical therapy. AEs such as hypertension and proteinuria warrant close monitoring.